Mechanisms of Action of MiRNAs and LncRNAs in Extracellular Vesicle in Atherosclerosis - Xu, Hui; Ni, Yu-Qing; Liu, You-Shuo (Frontiers in Cardiovascular Medicine, 2021)
Atherosclerosis, a complex chronic inflammatory disease, involves multiple alterations of diverse cells, including endothelial cells (ECs), vascular smooth muscle cells (VSMCs), monocytes, macrophages, dendritic cells (DCs), platelets, and even mesenchymal stem cells (MSCs). Globally, it is a common cause of morbidity as well as mortality. It leads to myocardial infarctions, stroke and disabling peripheral artery disease. Extracellular vesicles (EVs) are a heterogeneous group of cell-derived membranous structures that secreted by multiple cell types and play a central role in cell-to-cell communication by delivering various bioactive cargos, especially microRNAs (miRNAs) and long non-coding RNAs (lncRNAs). Emerging evidence demonstrated that miRNAs and lncRNAs in EVs are tightly associated with the initiation and development of atherosclerosis. In this review, we will outline and compile the cumulative roles of miRNAs and lncRNAs encapsulated in EVs derived from diverse cells in the progression of atherosclerosis. We also discuss intercellular communications via EVs. In addition, we focused on clinical applications and evaluation of miRNAs and lncRNAs in EVs as potential diagnostic biomarkers and therapeutic targets for atherosclerosis.